Serving a Larger Proportion of Vegetables and Fruits Improved Children's Intake Over 5 Days. (7th June 2021) - Sanchez, Christine; Roe, Liane; Keller, Kathleen; Rolls, Barbara
Abstract: Objectives: Although current guidelines recommend that vegetables and fruits make up half the diet, it is not known whether serving a greater proportion of vegetables and fruits will have sustained effects on children's consumption over multiple days. This study tested the effects on children's intake of two strategies for increasing the proportion of vegetables and fruits served over 5 days, either adding or substituting extra portions. Methods: In a crossover design with 3 periods, all meals and snacks for 5 days were provided to 3- to 5-year-old children in their childcare centers (n = 53; 47% girls; 16% with overweight). In the Baseline condition, typical portions for all food groups were served. In the Addition condition, the portions of vegetables and fruits were increased by 50% while other meal items remained unchanged, and in the Substitution condition, vegetable and fruit portions were increased by 50% while the portions of other foods were reduced. Vegetables and fruits provided 40% of the weight of food served in Baseline, 50% in Addition, and 60% in Substitution. All foods and beverages were weighed to determine daily intakes. Results: For vegetables, the Addition strategy increased daily intake compared to Baseline by 24% (12 ± 3 g; P = 0.0002) and the effect of Substitution was even greater with a 41% increase (22 ± 3 g; P < 0.001). These greater vegetable intakes were sustained across all 5 days by both strategies. For fruits, the two strategies increased overall daily intake by similar amounts: 33% by Addition (60 ± 6 g/d) and 38% by Substitution (69 ± 8 g/d; both P < 0.0001). For Substitution, this greater fruit intake was sustained across all 5 days; for Addition, mean daily fruit intake decreased across the 5 days (P < 0.0001) but was still greater than Baseline by 20% (34 ± 11 g; P = .004). Children's age and body mass index did not significantly affect vegetable and fruit intakes in response to serving greater proportions. Conclusions: Children's daily vegetable and fruit intakes increased when greater proportions were served, and these intakes were sustained above baseline for 5 days. These findings indicate that following dietary guidance to make vegetables and fruits half the diet can improve children's intake, especially when vegetables and fruits are substituted for other foods. Funding Sources: NIDDK.